Narcissism in Toronto: Jones, Freud, and minor differences. Issue 2 (1st February 2020) - Buse, Peter
ABSTRACT: This article conducts a genealogy of Freud's never fully developed concept of the narcissism of minor differences, which first appears in his writings in 1917, and then three more times with slight variations. It starts with an earlier articulation of the concept in 1908 in a letter from Ernest Jones in Canada to Freud. The article outlines the background to Jones' presence in Canada and his assessment of Canadians, and goes on to argue that in its subtle differences from Freud, Jones' version of the concept provides a clarification of what is essential in Freud's version. Among the questions it helps us answer is whether minor differences beget narcissism or narcissism cathects minor differences. In other words, tracing the path by which the idea develops tells us something interesting about its eventual shape. The article concludes that Freud does not so much borrow from Jones, as provide an analysis of Jones' letter through his modifications of it. The article finishes by arguing that the concept provides a different route into the philosophical and psychoanalytic question of the love of the neighbour, an issue central to the ethics of Jacques Lacan, and subsequently to Žižek and Santner.